MODEL FIXED-BED SEMI-FLOW SEBAGAI REAKTOR DALAM PROSES HIDRORENGKAH (STUDI KASUS: PERENGKAHAN KATALITIK DARIMINYAK KULIT JAMBU METE /CNSL): FIXED-BED SEMI-FLOW MODEL AS A DEEP REACTOR HYDRO CRACKING PROCESS (CASE STUDY: CATALYTIC CRACKING OF OIL CASHEW CASHEW SKIN / CNSL) - Darma Santi (JISTECH: Journal of Information Science and Technology, 2015)
The study of the reactor in the hydrocracking process still needs to be investigated. This related tothe control effort can be done in hydrocracking reaction with laboratory scale, which is catalytic andreactor functions. This review presents the performance of the reactor in residual percentage (%w/w)with the minimum is 1.78% for feed : catalyst ratio (6), and the percentage of conversion CashewNut Shell Liquid/CNSL that was carried out with the flow rate of H2 at 20 ml/min, the temperature of400oC and variation of the feed : catalyst ratio. The conversion products presented in liquid (themaximum is 65.31% for feed : catalyst ratio (6)), solid/coke (the maximum is 4.38% for feed : catalystratio (6)) and gas (the maximum is 49.35% for feed : catalyst ratio (2)).